Improved predator detection through illumination with red fluorescence by a small benthic fish. Does it work? - van der Schoot, Bram K. M.; Michiels, Nico K. (Frontiers in Ecology and Evolution, 2025)
BackgroundUsing controlled illumination to improve vision was believed to be limited to bioluminescent organisms in dark environments. Recent findings suggest that in shallow water, triplefins redirect sunlight to induce luminance contrast in the retroreflective pupils of nearby predators. At greater depths this mechanism becomes less effective. Triplefins, however, also possess red fluorescent irises. These may serve as an alternative light source to detect predator pupils in deeper waters by inducing a colour contrast. We tested whether triplefin iris fluorescence enhances the detection of predators.MethodsIn the first experiment, triplefins were exposed to a scorpionfish (predator) or a stone (control) under conditions that either allowed or prevented their iris fluorescence from illuminating the target. In the second experiment, triplefins were exposed to dummy scorpionfish with (1) retroreflective eyes, (2) non-retroreflective eyes, or (3) a live scorpionfish (control). In both experiments head bobbing was quantified as a known measure of caution.ResultsTriplefins bobbed more to live scorpionfish under all conditions, but significantly more when fluorescence could be used to illuminate the scorpionfish. Neither was the case for stones or (non-)retroreflective models. A weak fluorescence effect was found when comparing retroreflective versus non-retroreflective models.ConclusionsFluorescent irises may facilitate detection of retroreflective scorpionfish pupils. However, the weak response to the models suggests more than just retroreflection plays a role.